KESIAPAN ADOPSI INOVASI TEKNOLOGI PERIKANAN TANGKAP SEBAGAI DASAR PENGUATAN RESILIENSI NELAYAN SKALA KECIL DI PPI DUMAI: TECHNOLOGY ADOPTION READINESS IN CAPTURE FISHERIES AS A FOUNDATION FOR STRENGTHENING THE RESILIENCE OF SMALL-SCALE FISHERS AT DUMAI FISHING PORT - Putri Wangi Tri Rumelia; Zulkarnain; Trisla Warningsih; Irwan Effendi; Muhammad Natsir Kholis; Adriman (Fakultas Perikanan dan Ilmu Kelautan Universitas Satya Negara Indonesia, 2025)
This study analyzes readiness to adopt capture fisheries technology innovations as a basis for strengthening the resilience of small-scale fishers at Dumai Fishing Port. Technology readiness was assessed through three dimensions: fishing gear modernization, use of weather information systems, and digital marketing of fishery products. A survey method with qualitative and quantitative descriptive approaches was employed. Data were collected using a Likert-scale questionnaire administered to 20 fishers operating push nets (sondong), tidal traps (belat; gombang), and gillnets. The results showed that overall technology adoption readiness was moderate, with an average total score of 60.6. The weather information system dimension recorded the highest score (22.55), followed by fishing gear modernization (21.4), while digital marketing was the weakest dimension (16.65). These findings indicate that fishers recognize the benefits of technology for improving operational efficiency, safety at sea, market access, and competitiveness. However, adoption remains constrained by limited capital, technical knowledge, digital literacy, infrastructure, and institutional support. Technology adoption readiness can therefore serve as an entry point for strengthening fishers’ adaptive capacity and livelihood resilience. Affordable financing, practical training, improved digital and weather literacy, infrastructure development, and sustained institutional assistance are needed to support inclusive and locally appropriate technological transformation in coastal communities.